2012
DOI: 10.4161/auto.18806
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy inhibition promotes defective neosynthesized proteins storage in ALIS, and induces redirection toward proteasome processing and MHCI-restricted presentation

Abstract: Till Wenger and Seigo Terawaki contributed equally to this work; 4 Evelina Gatti and Philippe Pierre contributed equally to this work.Keywords: NBR1, SQSTM1, ATG5, antigen presentation, DRiPs A significant portion of newly synthesized protein fails to fold properly and is quickly degraded. These defective ribosomal products (DRiPs) are substrates for the ubiquitin-proteasome system (UPS) and give rise to a large fraction of peptides presented by major histocompatibility complex class I molecules (MHCI). Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…25 DALIS function as a reservoir for MHC I antigens and are putative substrates of autophagy. 26 Here, we detected ubiquitinated aggregates in the primary DC subsets using an antibody that recognizes poly-and mono-ubiquitinated proteins, but not free ubiquitin. Few ubiquitinated aggregates were present in either the immature DC subsets, or activated CD8 ¡ DC as measured by IFC.…”
Section: Resultsmentioning
confidence: 81%
“…25 DALIS function as a reservoir for MHC I antigens and are putative substrates of autophagy. 26 Here, we detected ubiquitinated aggregates in the primary DC subsets using an antibody that recognizes poly-and mono-ubiquitinated proteins, but not free ubiquitin. Few ubiquitinated aggregates were present in either the immature DC subsets, or activated CD8 ¡ DC as measured by IFC.…”
Section: Resultsmentioning
confidence: 81%
“…It involves de novo formation of a double membrane that sequesters a portion of the cytoplasm in an autophagosome, which then matures into a lytic vesicle (21). As for the ubiquitin/proteasome system, autophagy participates in quality control of protein aggregates and thus affects Ag presentation (22). In particular, defective ribosomal products (DRiPs), which constitute a source of Ag for MHC-I-restricted presentation, form aggregates that are degraded by both the ubiquitin/proteasome system and autophagy (22).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4mentioning
confidence: 99%
“…As for the ubiquitin/proteasome system, autophagy participates in quality control of protein aggregates and thus affects Ag presentation (22). In particular, defective ribosomal products (DRiPs), which constitute a source of Ag for MHC-I-restricted presentation, form aggregates that are degraded by both the ubiquitin/proteasome system and autophagy (22). Autophagy has been shown to contribute to presentation of HSV-1 and CMV Ags by MHC-I molecules (23,24).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4mentioning
confidence: 99%
“…Intracellular antigen presentation via MHC class I molecules is also regulated by the autophagy machinery, because autophagy‐related proteins enhance MHC class I internalization for degradation and thereby diminish antigen display on the cell surface 268. Indeed, in vivo studies have primarily found enhanced CD8 + T cell responses in mice with defective autophagy in antigen‐presenting cells268, 269, 270 A potential mechanism leading to such increased CD8 + T cell expansions is that, in the absence of autophagy, more substrate becomes available for canonical MHC class I loading271 or by decreased endocytosis and degradation of cell surface MHC class I molecules 268. Thus, defective autophagy in skeletal muscle fibers could drive increased MHC class I expression and CD8 + T cell accumulation.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%
“…The resulting peptides are fed into the MHC class I presenting pathway and will be surveilled by CD8 + T cells 287. Upon impairment of autophagy in HeLa cells, its substrates accumulate in p62/SQSTM1‐positive aggresome‐like induced structures and are fed into the proteasomal pathway with subsequent presentation via MHC class I 271. Differential activity of autophagy might, therefore, shape the peptide pool presented on MHC class I and it is tempting to speculate that impairment of this control mechanism in IBM muscle abets invasion of myoaggressive immune cells.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%